(untitled) (Al-Academy, 2016)
Summary Search Alachtgalat process semantic encoding carried out by the actor inside the theater to deliver the intellectual sense, and social, as well as the aesthetic to the recipient, the fact that the code is the function is operated relationship in accordance with the prior intent to deliver the implications of a particular intent, too, and the fact that encryption is the best way to transfer messages in system theater, where should the actor that has the ability to create images (sensory) or intellectual new in human consciousness on the basis of conversion of impressions collected from reality and re technically formed inside the theater, allowing the recipient to arrange these marks to obtain the meaning that lies in them. So he came to answer the question follows: How can the representative of the performance today produces blades recipient can then decode the implications, understand and communicate with them.Search section according to the following: where identified the problem of the research and its importance and its objectives and its borders and then the investigator should define the term blades in order to correct the search, then the theoretical framework came across two sections: the first, for semantic encoding and most prominent divisions theorists of the encryption process and the relationship of the code give indications. The second section dealt engage in semantic of the blade in the work of actor and how to establish a cipher. Find out after the set indicators can be a tool for the analysis of the sample. And then came the analysis in which the researcher eating a play (Romeo and Juliet in Baghdad) Sample. analysis. After analysis of the number of search results the most important output: - (for movement and gestures actor Representative building Chwira are references to a multi-cultural, psychological and social level of the character, they also contribute to enhancing the dramatic act and push it ahead). Then a list of sources relied upon in the search and finally the title and abstract in English